Constructing Sexual Fields: Chinese Gay Men's Dating Practices Among Pluralized Dating Apps. (April 2021) - Wu, Shangwei; Trottier, Daniel
In this study, we draw on sexual field theory to examine the structural nature of metropolitan Chinese gay men's mobile dating practices in a polymedia environment where one can access an array of dating apps. We define structures of desire in the sexual field as not only the transpersonal valuations of desirability but also the dominance of particular desires that coordinate actors' expectations and practices. Based on interviews with 52 urban Chinese gay men, we discuss the differing structures of desire hosted by four dating apps: Aloha, Blued, Grindr, and Tinder. Our analysis indicates that factors such as design features of dating apps, marketing strategies of app companies, and internet regulations have shaped the structures of desire by unevenly distributing the platform access to users across social classes and territorial divisions and (dis)enabling particular communicative practices in collective sexual life to different extents. The distance-sorted display of nearby users contributes to the predominance of immediate hook-ups on Blued and Grindr, while the matching mechanism of Aloha and Tinder functions as a "speed bump" and nourishes users' expectations for lasting connections. As Blued is the most popular gay dating app on the heavily guarded Chinese internet market, the diversity of its users drives away many metropolitan middle-class gay men who only desire their own kind. In comparison, Aloha, Grindr, and Tinder, with smaller user bases, are more specialized sexual sites where the dominant currency of sexual capital reflects the middle-class standard for "quality."